Post-Holocaust Migrations of Empathy: My Star by Felicja Raszkin-Nowak - Janicka, Anna (Porównania, 2023)
Felicja Raszkin-Nowak still remains a little-known witness of the Holocaust. Born in Warsaw, she found herself in Białystok as a little girl during the war. Miraculously she survived the liquidation of the ghetto and hid on a farm, from where she was liberated. After the war, she worked at Polish Radio, and after March 1968 she emigrated to Denmark. In 1991, she published her memoirs titled My Star, translated into several languages. They are a faithful and shocking portrayal of war and the Holocaust, written with rare mastery. Raszkin-Nowak’s writing strategy combines several different perspectives: that of a child and an adult, a Polish woman and a Jew, a girl and a mature woman on the threshold of old age. Raszkin-Nowak uses an innovative storytelling technique that can be called empathetic realism. It enables the author to overcome the internal and external distance between the experience of childhood and the experience of war, the experience of cultural settlement and the experience of emigration, the time of events and the time of reminiscing.